2000
DOI: 10.1038/sj.bmt.1702432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors for allogeneic marrow transplantation following busulfan and cyclophosphamide in myelodysplastic syndrome and after leukemic transformation

Abstract: Summary:Prognostic factors in 42 patients aged 11 to 62 (median 46) years, with myelodysplastic syndrome (MDS) or after leukemic transformation, who underwent allogeneic marrow transplantation between 1984 and 1999 were analyzed. Thirty-six had advanced disease morphology; 19 had leukemic transformation. Twenty-nine received a preparative regimen of BuCy 2 and 13 busulfan 14 mg/kg, etoposide 50 mg/kg and cyclophosphamide 120 mg/kg. Severe hepatic veno-occlusive disease (VOD) occurred in three patients all of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…8,27,28 In the multivariate analysis for OS, age X45 years correlated with decreased survival. The risk of death increased by a factor of 1.57 (57%) per decade.…”
Section: Discussionmentioning
confidence: 99%
“…8,27,28 In the multivariate analysis for OS, age X45 years correlated with decreased survival. The risk of death increased by a factor of 1.57 (57%) per decade.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Recent literature has indicated that performance status of transplant recipients, rather than recipient age per se, may be a better indicator of the ability of a patient to tolerate allo-HSCT. The Charlson comorbidity index, adapted for HSCT, has been shown to predict NRM in patients receiving allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, it has been shown that in the allogeneic transplantation setting for MDS patients, there is a high transplant-related mortality (TRM). [7][8][9][10][11][12] Other authors have observed that faster engraftment is achieved in hematological malignancies when PB is used as the cell source instead of BM. 14,15 Based on these findings, special attention was paid to differences between BM and PB as a source of HSCT in the present series.…”
mentioning
confidence: 99%
“…5,6 Several risk factors predicting clinical evolution after allogeneic transplantation have been described such as disease stage, proportion of blast cells in BM, age, cytogenetic aberrations, disease duration and IPSS score. [7][8][9][10][11][12][13] The present report analyzes the outcome of 81 patients who have been reported to the Spanish registry for hematopoietic cell transplantation (Grupo Espan˜ol de Trasplante Hematopoye´tico, GETH), who underwent an allogeneic transplant from an HLA-identical sibling donor. In previous reports, it has been shown that in the allogeneic transplantation setting for MDS patients, there is a high transplant-related mortality (TRM).…”
mentioning
confidence: 99%